Bacillus amyloliquefaciens alleviates the pathological injuries in mice infected with Schistosoma japonicum by modulating intestinal microbiome - Chen, Hao; Sun, Ruizheng; Wang, Jingyan; Yao, Siqi; Batool, Syeda Sundas; Yu, Zheng; Huang, Shuaiqin; Huang, Jing (Frontiers in Cellular and Infection Microbiology, 2023)
Schistosoma japonicum causes serious pathological organ damage and alteration of the intestinal microbiome in the mammalian host, threatening the health of millions of people in China. Bacillus amyloliquefaciens has been reported to be able to alleviate the damage of gut and liver, and maintain the homeostasis of intestinal microenvironment. However, it was unclear whether B. amyloliquefaciens has the ability to alleviate the hepatic and intestinal symptoms caused by S. japonicum. In this study, the intragastric administration of B. amyloliquefaciens was performed to treat S. japonicum-infected mice during the acute phase. Histopathological analysis and 16S rRNA gene sequencing were used to evaluate the pathological damage and changes in the intestinal microbiome. The results of the study showed that B. amyloliquefaciens treatment significantly reduced the degree of granuloma and fibrosis in infected mice. Additionally, recovery of diversity in intestinal microbiome, decrease in relative abundance of potential pathogenic bacteria like Escherichia-Shigella, and reshaping of interactive network between genera in the intestine were also observed after treating with B. amyloliquefaciens. Our findings indicated that treatment with B. amyloliquefaciens effectively alleviated the pathological injuries of liver and intestine in mice infected with S. japonicum by modulating intestinal microbiome, implying that this probiotic has the potential to function as an effective therapeutic agent against schistosomiasis. We hope our study will provide auxiliary strategy and methods for the early prevention of schistosomiasis japonica.